British constitution: a very short introduction - Loughlin, Martin (New York, 2013)
The British constitution is regarded as unique among the constitutions of the world. What are the main characteristics of Britain's peculiar constitutional arrangements? How has the British constitution altered in response to the changing nature of its state - from England, to Britain, to the United Kingdom? What impact has the UK's developing relations with the European Union caused? These are some of the questions that Martin Loughlin addresses in this Very Short Introduction. As a constitution, it is one that has grown organically in response to changes in the economic, political, and social environment, and which is not contained in a single authoritative text. By considering the nature and authority of the current British constitution, and placing it in the context of others, Loughlin considers how the traditional idea of a constitution came to be retained, what problems have been generated as a result of adapting a traditional approach in a modern political world, looking at what the future prospects for the British constitution are. ABOUT THE SERIES: The Very Short Introductions series from Oxford University Press contains hundreds of titles in almost every subject area. These pocket-sized books are the perfect way to get ahead in a new subject quickly. Our expert authors combine facts, analysis, perspective, new ideas, and enthusiasm to make interesting and challenging topics highly readable.
Keywords: "Constitutional history Britain, Political science"